2014
DOI: 10.1021/np5002829
|View full text |Cite
|
Sign up to set email alerts
|

Limonoids from the Seeds of Swietenia macrophylla with Inhibitory Activity against Dengue Virus 2

Abstract: Fractionation of an ethanol-soluble extract of the seeds of Swietenia macrophylla yielded six new limonoids, swielimonoids A-F (1-6), along with 20 known compounds. Compounds 1 and 2, mexicanolide-type limonoids, were assigned with an α,β-unsaturated δ-lactone moiety (ring D) and a C═C bond between C-8 and C-30. Compounds 3-6 could be categorized as highly oxygenated phragmalin-type limonoids. The structures of these new compounds were elucidated through the interpretation of spectroscopic data. The antidengue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…Therefore, the molecular diversity of the isolates and three anti-dengue virus datasets was analyzed by the ChemGPS–NP map of chemical space. The first dataset consisted of the seventeen anti-dengue virus ecdysteroids isolated from zoanthids; the second dataset contained eight anti-dengue virus limonoids separated from Swietenia macrophylla [25]; and the third dataset composed of twelve non-peptidic anti-dengue virus compounds [26,27]. The score plot of three descriptors (PC1, PC2, and PC4) revealing that peridinin ( 9 ), limonoids, and ecdysteroids situated in the same quadrant (Figure 5), and, meanwhile, peridinin and limonoids occupied the same quadrant while the descriptors changed to PC1, PC2, and PC3.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the molecular diversity of the isolates and three anti-dengue virus datasets was analyzed by the ChemGPS–NP map of chemical space. The first dataset consisted of the seventeen anti-dengue virus ecdysteroids isolated from zoanthids; the second dataset contained eight anti-dengue virus limonoids separated from Swietenia macrophylla [25]; and the third dataset composed of twelve non-peptidic anti-dengue virus compounds [26,27]. The score plot of three descriptors (PC1, PC2, and PC4) revealing that peridinin ( 9 ), limonoids, and ecdysteroids situated in the same quadrant (Figure 5), and, meanwhile, peridinin and limonoids occupied the same quadrant while the descriptors changed to PC1, PC2, and PC3.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that compound 24 exhibited good antibacterial potency against Bacillus subtilis and good antifungal activity against Aspergillus niger with observed zones of inhibition of 15.2 ± 0.50 mm and 17.3 ± 0.49 mm, respectively . Furthermore, compound 24 showed an anti dengue virus 2 (DENV‐2) inhibitory activity with an EC 50 of 4.3 ± 2.31 μ m …”
Section: Antimicrobialmentioning
confidence: 99%
“…It is important to mention that to the best of our knowledge, no work has been done on the study of the action mechanisms and pharmacokinetics of isolated active compounds from the genus Entandrophragma. The knowledge Table 8 Cytotoxicity activity of some metabolites Compound Cells and activity Azadirone (1) MCF7/ADR, GI 50 = 0.06 lM [131] U251, GI 50 = 2.5 lM [131] SW620, GI 50 = 7 lM [131] H522, GI 50 = 6 lM [131] M14, GI 50 = 0.08 lM [131] SKOV3, GI 50 = 5 lM [131] DU145, GI 50 = 0.05 lM [131] A498, GI 50 = 2 lM [131] Gedunin (12) HepG2, IC 50 = 0.76 lM [132] SKBr3, IC 50 = 3.22 lM [133] MCF7, IC 50 = 8.84 lM [133] HL60, IC 50 = 5.9 lM [134] AZ521, IC 50 = 16.9 lM [134] P388, IC 50 = 3.3 lM [135] A549, IC 50 > 20 lM [134] CRL1579, IC 50 > 20 lM [134] 11b-acetoxygedunin (13) P388, IC 50 = 3.8 lM [135] Methyl angolensate (24) Huh-7, CC 50 = 116 lM [81] epoxyazadiradione (nimbinin) (3) GPK, ED 50 = 7.13 lg/ml [73] KB, IC 50 = 12.87 lg/ml [75] NCI-H187, IC 50 = 7.54 lg/ml [75] MCF7, IC 50 = 4.68 lg/ml [75] N1 9 10 -115 , IC 50 = 23 lM [131] 143B.TK, IC 50 L6, IC 50 = 11.0 lM [5] Prototiamin F (114) L6, IC 50 = 6.5 lM [5] Prototiamin G (115) L6, IC 50 = 8.6 lM [5] Seco-tiaminic acid A (95) L6, IC 50 = 56.1 lM [5] Seco-tiaminic acid B (99) L6, IC 50 = 9.5 lg/ml [31] Seco-tiaminic acid C (100) L6, IC 50 = 10.6 lg/ml…”
Section: Concluding Notes and Future Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Limonoids derived from tetracyclic triterpenes eufol like (H-20β) or tirucalol (H-20α) by a series of oxidative changes, interspersed with molecular rearrangements (7). Most of the limonoids that have been evaluated were obtained from seed extracts (8).…”
Section: Introductionmentioning
confidence: 99%